2021
DOI: 10.3389/fnins.2021.675444
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Involvement in Amyotrophic Lateral Sclerosis: A Combined Structural and Diffusion Tensor MRI Analysis

Abstract: IntroductionThe brainstem is an important component in the pathology of amyotrophic lateral sclerosis (ALS). Although neuroimaging studies have shown multiple structural changes in ALS patients, few studies have investigated structural alterations in the brainstem. Herein, we compared the brainstem structure between patients with ALS and healthy controls.MethodsA total of 33 patients with ALS and 33 healthy controls were recruited in this study. T1-weighted and diffusion tensor imaging (DTI) were acquired on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Prior to further processing images, quality checks on diffusion images were performed using QUAD and SQUAD, the automated quality control tool in FSL ( 79 ). Results indicated that all participants fell under the exclusion threshold from previous literature, which was average volume-to-volume head motion of <3 mm or <5% of total outliers ( 80 , 81 ). Visual inspection on the cleaned images confirmed this result, but because diffusion images are especially susceptible to head motion ( 82 ), head motion effects were further tested, as discussed in Control Analyses .…”
Section: Methodsmentioning
confidence: 78%
“…Prior to further processing images, quality checks on diffusion images were performed using QUAD and SQUAD, the automated quality control tool in FSL ( 79 ). Results indicated that all participants fell under the exclusion threshold from previous literature, which was average volume-to-volume head motion of <3 mm or <5% of total outliers ( 80 , 81 ). Visual inspection on the cleaned images confirmed this result, but because diffusion images are especially susceptible to head motion ( 82 ), head motion effects were further tested, as discussed in Control Analyses .…”
Section: Methodsmentioning
confidence: 78%
“…Unlike in interesting previous studies that first applied this approach, 26,27 we focused our cluster-based analysis on CNS-selected areas that are already found to be associated with survival 20,22 and disease severity. 17,21,40 Restricting the cluster-based analysis to the motor cortical areas and medulla oblongata, we first found that a considerable proportion (57%) of patients with ALS (belonging to cluster 2) showed greater involvement of the medulla already at the time of diagnosis. Second, a small subgroup of the ALS cohort (cluster 3, 12%) had early involvement of the motor and extramotor cortices with relative preservation of the medulla oblongata.…”
Section: Discussionmentioning
confidence: 99%
“…13 Specifically, disease severity (expressed as ALS Functional Rating Scale-Revised [ALSFRS-r] score) and progression rate correlated with the mean cortical thickness of the motor area, [14][15][16][17][18] extramotor areas (eg, paracentral lobules), 17,19 and medulla oblongata volume (MOv). [19][20][21] These MR imaging metrics have also been proposed as predictive biomarkers of survival. 20,22 Nonetheless, most imaging studies validated MR imaging metrics by describing phenotype-, genotype-, or stage-associated radiologic profiles [23][24][25] in a priori selected clinical categorizations (eg, spinal or bulbar onset, fast and slow progressors, prevalent upper or lower motor neuron impairment).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Magnetic Resonance (NMR) spectroscopy is a highly effective analytical tool for providing intricate details about the molecular structure, composition, and dynamics of a sample. It has also given rise to many new techniques, including Magnetic Resonance Spectrometry (MRS), Nuclear Magnetic Resonance Imaging (MRI), Functional MRI (fMRI), Diffusion MRI (dMRI), and Diffusion Tensor Imaging (DTI) [1][2][3][4][5] . These NMR techniques find widespread applications in fields such as chemistry, biology, agriculture, and medicine [6][7][8][9] .…”
Section: Overview Of Nmr Techniquesmentioning
confidence: 99%